The Effect of Group Counseling Program in Decreasing Anxiety and Improving Parental Competence Among Mothers of Children With Behavioral Problems - Alaedein, Jehad; Taraweneh, Amany (Jordan Journal of Educational Sciences, 2019)
This study aimed to investigate the effect of a group-counseling program in decreasing levels of anxiety and improving parental competence among a sample of Jordanian mothers of children with behavioral problems. Those mothers sought professional help for their child's difficulties from The Family Awareness and Guidance Center, New Zarqa, Jordan. The participants consisted of (32) mothers; they were selected according to their scores on anxiety and parental competence scales, and they were randomly assigned to two groups; the experimental group (N = 16) and the control group (N = 16). The results of pre-test to post-test differences for the experimental and control groups on the study scales revealed that the treatment group compared to control group was significantly more likely to have lower anxiety and higher parental competence. Furthermore, the results of post-follow-up tests comparison for each of the dependent variables for treatment group showed that differences were significant on scales of the two study. In particular, the results in the follow-up tests show that the scores on the anxiety scale were positively decreased, while on the parental competence scale were higher